2018
DOI: 10.1530/eje-17-0634
|View full text |Cite
|
Sign up to set email alerts
|

Somatic USP8 mutations are frequent events in corticotroph tumor progression causing Nelson’s tumor

Abstract: Somatic mutations in are common in Nelson's tumors, indicating that they do not drive the corticotroph tumor progression that leads to NS, and may be associated with a less favorable biochemical outcome after surgery for Nelson's tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 37 publications
(69 reference statements)
0
40
2
1
Order By: Relevance
“…Previous studies have postulated a role for USP8 mutational status as predictor of long‐term remission. Patients with USP8 mutant tumours presented with higher 24‐hours‐UFC levels and impaired ACTH reduction after surgery, and paediatric CD patients with USP8 mutant tumours showed higher recurrence rate . Another study suggested a shorter mean recurrence period in USP8 mutants (months 29 vs 48) in a subset of adult CD patients that recurred .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have postulated a role for USP8 mutational status as predictor of long‐term remission. Patients with USP8 mutant tumours presented with higher 24‐hours‐UFC levels and impaired ACTH reduction after surgery, and paediatric CD patients with USP8 mutant tumours showed higher recurrence rate . Another study suggested a shorter mean recurrence period in USP8 mutants (months 29 vs 48) in a subset of adult CD patients that recurred .…”
Section: Discussionmentioning
confidence: 99%
“…CD tumours bearing USP8 mutations were reported to be smaller in size and less invasive . At the same time, we have shown higher 24‐hour urinary‐free cortisol (UFC) levels and impaired ACTH reduction after surgery in patients with USP8 mutant tumours, suggesting that they may present with higher rate of recurrence . Indeed, a study on paediatric CD patients reported higher recurrence rate in those with USP8 mutant tumours .…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Nevertheless, owing to elevated proliferative index and enhanced invasive growth, Nelson’s tumors can evolve to carcinomas in rare cases 66 . There is no evidence for a common specific genetic background leading to the formation of Nelson’s tumors, and in a recent study the proportion of USP8 mutations (45%) was found to be similar to that of corticotroph tumors in general 35 . Thus, the mechanisms triggering the development of Nelson’s tumors are still unknown 64, 65 .…”
Section: Progression Of Corticotroph Adenomasmentioning
confidence: 98%
“…In a recent study, a lower incidence of USP8 mutations was found in children with Cushing’s disease compared with adults 33, 34 . Whereas the prevalence of USP8 mutations was reduced in Crooke’s cell adenomas 26 , the proportion of mutant USP8 in so-called Nelson’s tumors (see the “Corticotroph pituitary tumor types” section) was identical to that in corticotropinomas in general 35 . Patients with USP8 mutations were diagnosed significantly earlier and had higher preoperative 24-hour urinary-free cortisol levels 36 .…”
Section: Genetic and Epigenetic Modifications In Sporadic Corticotropmentioning
confidence: 99%